Training in Metacognitive Strategies for Students' Vocabulary Improvement by Using Learning Journals - Itala Diaz (Universidad Nacional de Colombia, 2015)
This study examined the effects of metacognitive strategies to help beginning young learners with difficulties increasing and retaining vocabulary. This was a qualitative study in which participants first went through metacognitive strategy instruction to provide awareness of learning strategies. Following this instruction, students underwent a set of five interventions based on the cognitive academic language learning approach instructional model. These interventions, together with journaling progress, were used to train them in the use of the metacognitive strategies planning, monitoring, and evaluating. The findings showed that metacognitive strategy training has positively contributed to vocabulary acquisition skills, as participants were able to raise consciousness about some learning strategies and the use of metacognitive strategies to increase their vocabulary learning.